ACADEMIC MOBILITY IN THE ERA OF TURBULENCE - Iryna Kalenyuk; Deniss Djakon (Izdevnieciba "Baltija Publishing", 2022)
The relevance of the problems of international academic mobility is due to the growth of export-import of educational services, aggravation of the global level of competition for human and intellectual resources. In the 20s of the 21st century new challenges emerged (COVID-19 pandemic, Russian aggression in Ukraine), which led to a serious transformation of the European and global educational space. In this context, the issue of developing tools to minimize negative challenges while intensifying the processes of academic mobility is relevant. The aim of the article is to analyze the processes of academic mobility in the context of contemporary challenges, in particular, the consequences of Russian aggression on the processes of international migration, redistribution of the global and European higher education market, development of university cooperation in the European and global educational environment. A common trend in higher education is dynamic internationalization: between 2000 and 2019, the number of students worldwide just over doubled (by 235%), and the number of international students tripled from 2.088 million to 6.064 million. And in traditional regions the number of foreign students increased 2-2.5 times (in Europe - 246%, in North America - 221%), and in rapidly developing regions - 4-8 times (in Asia - 440%, South America - 828%, Oceania - 481%). The consequences of the pandemic have been the increased penetration of ICTs in educational processes, the diversification of forms and methods of learning, and the spread of "internationalization at home". The military aggression of 2022 provoked a rapid increase in academic mobility, increased flows from Ukraine, and the exclusion of the Russian Federation from the European and global educational community: all programs and grants were suspended, all opportunities for academic mobility were closed, and it was excluded from the Bologna Process. European and other Western countries have taken unprecedented measures to support students and scholars, both at the level of countries and associations, as well as by individual universities. The consequence of Russian aggression has been a dynamic change in the flow of academic mobility, the main manifestation of which will be a significant influx of students and scholars to European and other countries.